Using English pronunciation websites to improve students' pronunciation: an action research project at an English center in Hanoi = Sử dụng trang web dạy phát âm tiếng Anh để cải thiện khả năng phát âm của học sinh. M.A Thesis Linguistics: 8140 - Nguyễn, Thị Loan (2019)
This study investigated the potential role of pronunciation websites as a means to improve students‘ competence in pronunciation. The research aimed to figure out whether the use of pronunciation instruction websites could help improve students‘ pronunciation and to identify students‘ attitude towards using these websites as well as the selected activities. In order to accomplish these purposes, 15 students of class Movers 6 at an English center in Hanoi were selected to participate in the study.